Efficient visible-light photocatalysis of ZIF-derived mesoporous ZnFe2O4/ZnO nanocomposite prepared by a two-step calcination method. (April 2018) - Hu, Pengfei; Chen, Changchun; Song, Jiawei; Tang, Zhonghai
Abstract: Specific surface area of photocatalyst usually has an important influence on its photocatalytic performance. Herein, mesoporous ZnFe2 O4 /ZnO nanocomposites were successfully fabricated by facile calcination methods using ZnFe2 O4 /ZIF-8 as the precursor. The structure, morphology, optical and adsorption properties of the as-prepared samples were detailedly characterized, and photocatalytic performances of these samples were mainly evaluated by the degradation of Rhodamine B (RhB) under visible light irradiation (λ > 400 nm). The results demonstrated that the ZnFe2 O4 /ZnO hybrids are of enhanced visible-light photocatalytic performances among all the samples, indicating that the heterojunction structure between ZnFe2 O4 and ZnO efficiently inhibited the the recombination of photogenerated electron-hole pairs. Wherein, the ZFO/C6A4 sample prepared via two-step calcination method (600 °C in Ar and then 400 °C in air ambient) possessed higher visible light photocatalytic activity than the ZFO/A6 sample prepared via one-step calcination (600 °C in air ambient). This phenomenon was probably ascribed to the lager pore volume and average pore size of ZFO/C6A4 sample. Moreover, the potential carbon doping in ZnO particles during two-step calcination process was inferred by the XRD analysis, which further facilitated the separation of photogenerated electron-hole pairs in the ZFO/C6A4 sample. On the other hand, the composite sample also exhibited good magnetic recovery property and photochemical stability. These results indicated that the ZnFe2 O4 /ZnO nanocomposite prepared via two-step calcination method would be quite promising for the degradation of organic pollutants.